Pakistan 2005 - edited by Charles H. Kennedy; Cynthi A. Botteron (Oxford University Press, 2006)
Pakistan 2005 provides a readily accessible overview of current politics, foreign policy and economic issues which face one of Asia's most rapidly-growing and important nation-states. The volume contains eight essays crafted by some of the best-known specialists in the region. It is aimed at the non-specialist audience although academics and policy-makers will find the volume useful